English language learning anxiety and academic burnout in Chinese freshmen: a chain mediating approach - Zheng, Shuang; Zhang, Junliang; Wang, Jingming; Shen, Ruiqing (Frontiers in Psychology, 2024)
Background:The university stage is critical for cultivating and enhancing students' practical English proficiency, encompassing listening, speaking, reading, writing, and translation skills.Losing interest in English studies at this stage not only hampers the development of practical English competence but also has a negative impact on future employment and personal growth. Aims:This study aimed to explore to how English language learning anxiety (ELLA) affects academic burnout(AB) of freshman in China and explores the role of academic peer support (APS) and academic self-efficacy (ASE) in the relationship between the two. Methods:The study involved 1,355 college students who completed English Language Learning Anxiety Scale , the English Academic burnout Scale,Academic Peer Relationship Scale,the Academic Self-efficacy Scale . Results:AB was significantly impacted by ELLA.ELLA and AB were mediated by ASE. Another factor that acted as a mediator between ELLA and AB was APS. ELLA and AB were mediated by a chain reaction involving ASE and APS.The chain mediation model validated in this study, providing valuable insights into the effects of freshmen's ELLA on AB in China, as well as practical insights into the prevention and intervention of ELLA and AB in other current college students.